The Influence of the Culture of Thanksgiving and Tolerance on the Harmony of the People in the Parish of the Resurrection of Christ Amurang - Hadi Ignatius Untu; Murtiaty G. M. Sumolang (Journal La Sociale, 2023)
The Minahasa people have one of the most famous cultures, the culture of thanksgiving. This culture has been going on for generations where all Minahasa people from all religious groups jointly and harmoniously offer the harvest as a form of gratitude for the blessings of God Almighty. This study aims to see the influence of the culture of thanksgiving and tolerance on the harmony of the people in the Parish of the Resurrection of Christ Amurang. The method used is quantitative method and data analysis using multiple linear regression. From the results of this study, it is known that the significant value is 0.000 with an R Square value of 0.800. This shows that there is a positive and significant influence of the culture of thanksgiving and tolerance on the harmony of the people in the Parish of the Resurrection of Christ Amurang.